NILAI RETENSI NITROGEN DAN ENERGI METABOLIS BROILER YANG DIBERI RANSUM TEPUNG LIMBAH SAWI PUTIH (Brassica rapa L. subsp. pekinensis) - The, Fransisca; Mandey, J S; Kowel, Y H.S; Regar, M N (ZOOTEC, 2017)
ABSTRACT THE VALUE OF NITROGEN RETENTION AND METABOLIZABLE ENERGY OF BROILER DIETS WITH MUSTARD MEAL (Brassica rapa L. subsp. pekinensis) This research was conducted to determine the value of nitrogen retention (NR) and nitrogen corrected metabolizable energy value (AMEn) of broiler diets containing waste of mustard meal. Research used 18 MB 202 of broiler chickens 6 weeks of age that consists of 3 days of preliminary and 3 days collecting data. The experimental wasdesigned by a completely randomized design (CRD), which consists of 3 treatments and 6 replications. The treatmentswere: R0 = 100% based diet (BD) + 0% mustard waste meal (MWM), R1 = 90% BD + 10% MWM, and R2 = 80% BD + 20% MWM. Variables were nitrogen retention (NR) and metabolizable energy nitrogen corrected (AMEN) value. Results showed that the NR value was significantly (P <0.05) affected by treatments and the AMEn was highly significant (P <0.01) affected by treatments. HSD test showed thatthe NR value of R1(54,59%) and R2 (41,71%) was significantly decreased compared to control (41,71%).The AMEn value oftreatment R1 (2504.07 Kcal/kg) and R2 (2117.00Kcal/kg) was signicantly decreased compared to R0 (3141.57 Kcal/kg). Based on the NR and AMEn values, it can be concluded that mustard waste could be used up to 10% in dietof broilers Keywords : broiler, metabolizable energy,mustard, nitrogen retention,